The Influence of Islamic Education on the Formation of Sustainable Character in Students in the 21st Century: Literature Review Study - Najwa Zuhrotul Auliya; Siti Nur Saniya; Nihayatul Ilmiyah; Wulandaroini Sucianingsih; Sirojuddin Abror (STAI Asy-Syukriyyah, 2026)
The 21st century is marked by rapid technological developments and globalization, which have transformed the mindsets and behaviors of the younger generation. Easy access to information creates serious challenges in the form of moral degradation in students, such as a decline in respect, responsibility, honesty, and social awareness. This article aims to analyze the influence of Islamic education on the formation of sustainable character in students. The research uses a quantitative descriptive approach based on a literature review of 15 relevant scientific journals. Indicators of Islamic education include religious activities, worship habits, educator role models, and moral learning. The analysis shows that Islamic education has an average influence of 25% on the formation of sustainable character. Religious activities contribute the highest (30%), followed by worship habits (25%), educator role models (22%), and moral learning (23%). In conclusion, Islamic education has a significant influence and plays a strategic role in shaping a strong character that remains consistent throughout life and is resilient in the face of the challenges of the 21st century.